Productivity Analysis A Range of Perspectives - Dogramaci, Ali (Springer Netherlands, 1981)
There is a wide variety of perspectives for productivity analysis. The back grounds of different researchers and practitioners who work on this topic include such fields as economics, business administration, and industrial engineering, among others. Within each such field, there are different schools of thought on the theory and application of productivity analysis. Often it is not difficult to observe a lack of communication among the advocates of these separate schools. The purpose of this book is to present in a single volume samples of alternative approaches to productivity analy sis. This may be considered as a first step toward a better communication among practitioners and researchers in the fields of management, industrial engineering, and economics. The focus of the book is on the United States, where the productivity growth problem has been acute for some time. The book begins with a brief overview chapter that covers some of the issues involved in productivity analysis and a sample of methodological ap proaches presently in use. After this introduction, we move to Chapter 2 where Solomon Fabricant presents the issues related to measurement and analysis at the macroeconomic level. In Chapter 3, C. Lowell Harriss discusses concepts that he considers es sential for productivity growth: capital formation, technological progress, and freedom
Keywords: Operations Research/Decision Theory; Operations Management; Operations research; Decision making; Production management; Produktivität; Industrie; Analyse; USA